THALASSEMIA AND BLOOD GROUPS: IS THERE AN ASSOCIATION? - QIDWAI , A; SYEDA , A; KIDWAI , A; AHMAD , F; KHALIL , W; PASHA , N; ZEHRA , K (Biological and Clinical Sciences Research Journal, 2024)
Thalassemia major is a severe hereditary blood disorder that poses significant health challenges, particularly in regions with high prevalence rates. The distribution of thalassemia major has been observed to vary with ethnicity and blood group, yet few studies have explored these associations within the Pakistani population. Objective: This study aimed to determine the association between thalassemia major, blood groups, and ethnicity among the Pakistani population. Methods: This case-control study was conducted retrospectively using data from a Thalassemia center in Karachi, Pakistan. The study included a total sample size of 1,471 participants, with 731 (49.7%) identified as cases with thalassemia major and 740 (50.3%) as controls from December 2023 to May 2024. Participants were recruited using a convenience sampling technique, and those with incomplete data were excluded. Data were retrieved from an EMR suite, with prior approval from the institutional review board, and all information was identified to ensure confidentiality. Data analysis was performed using SPSS version 26, with descriptive statistics for numerical data and frequency and percentages for categorical data. The association between categorical variables was assessed using the Chi-square test, and odds ratios (OR) were calculated to evaluate the relationship between blood groups and thalassemia major. A p-value of less than 0.05 was considered statistically significant. Results: The study found a statistically significant association between ethnicity and thalassemia major (p = 0.0001). Among the cases, 52.6% were Balochis, 43.1% Sindhi, 64.3% Punjabi, 46.3% Mohajir, 47.7% Pushtoon, 60.9% Gujrati, and 100% Kashmiri. The blood group A positive showed the highest association with thalassemia major (OR 1.49, CI 1.19-1.87), while O positive, O negative, and B negative blood groups were also positively associated. Other blood groups demonstrated a protective association against thalassemia major. Conclusion: The study concluded that blood groups A positive, O positive, O negative, and B negative are positively associated with thalassemia major, while the Bombay blood group showed the most protective association. Additionally, there was a statistically significant association between ethnicity and thalassemia major, emphasizing the importance of considering both blood group and ethnicity in understanding the distribution of this condition in the Pakistani population.